Hubungan Literasi Finansial dengan Kesejahteraan Finansial di Kalangan Generasi Z Masyarakat Kelurahan Kalibaru Kota Bekasi - Alina Alifah; Ferdy Muzzamil; Rizma Afian Azhiim (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the relationship between financial literacy and financial well-being among Generation Z in Kalibaru Village, Bekasi City. Rapid digitalization and increasing access to financial services have created both opportunities and challenges for young people in managing their finances. This research employed a quantitative correlational design with 348 respondents selected through accidental sampling. Financial literacy was measured using a scale adapted from Lusardi and Mitchell, while financial well-being was assessed using the Consumer Financial Protection Bureau (CFPB) Financial Well-Being Scale. Data were analyzed using Spearmanâ€™s rho correlation test. The results indicated a significant positive relationship between financial literacy and financial well-being (râ‚› = 0.709; p 0.001). These findings suggest that higher financial literacy is associated with higher perceived financial well-being among Generation Z. This study highlights the importance of financial literacy education in enhancing economic and psychological well-being among young people.